An in-situ, fiber-optic system for sub-surface, environmental dose measurements using radiophotoluminescence from Ag-doped alkali-phosphate glass. (March 2020) - McKeever, S.W.S.; Sholom, S.; Shrestha, N.; Klein, D.M.
Abstract: The feasibility of using radiophotoluminescence from Ag-doped alkali-phosphate glass as an in-situ, sub-surface environmental radiation monitor is examined. GD-302M glass from Chiyoda Technol Corporation was attached to the end of a silica optical fiber inside a stainless-steel probe and inserted into soil to a depth of ~1 m. Radiophotoluminescence (RPL) from the GD-302M detectors was stimulated along the fiber using a 355 nm pulsed laser and RPL emission was directed along the same fiber and detected by a photomultiplier tube. Restrictions on the average laser power to be used in the experiments were observed due to the creation of an RPL signal for a zero-dose sample, or depletion of the radiation-induced signal from an irradiated sample. Short (1 s), low-frequency (1 kHz) laser stimulation rendered such effects negligible, while providing sufficient sensitivity to enable measurements of environmental doses of ~100 μGy. Highlights: Development of an  in-situ  probe for sub-surface environmental dosimetry using radiophotoluminescence. Ag-doped alkali phosphate glass. Minimum measurable dose of ~100 microGy. Effects of laser power on the RPL readout.